MINAT BELAJAR SISWA KELAS VIII TERHADAP MATA PELAJARAN IPA DI MTs. PP. HASANATUL BAROKAH TAMBUSAI TIMUR TAHUN PEMBELAJARAN 2014 / 2015 - Yunita, Rahmah; Lestari, Rena; Brahmana, Eti Meirina (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
The aim study of this was to know the student learning interest in class VIII to IPA subjects. This is a descriptivestudy. Samples were collected with random sampling techniques. Based on research and analysis that has beendone we can conclude that interest students class learning VIII MTs. PP. Hasanatul Barokah Tambusai Timurat 78% with high criteria.